Safety and side effects of propofol in clinical practice - literature overview - Maciej Lambach; Gabriela Demidowicz; Natalia Trąbka; Klaudia Kowalczyk; Nina Lasota; Wojciech Wiśniewski; Małgorzata Chyćko; Julia Czarnota; Katarzyna Cichoń; Martyna Younes (Kazimierz Wielki University, 2023)
Introduction and purpose Since people have been conducting surgeries to improve their health, they have always faced the problem of pain that these actions inevitably bring. Propofol as an anesetic is one of the solutions to these problems. Due to the widespread use of this drug, its side effects are often observed. This paper aims to gather the available knowledge about the adverse reactions of propofol in clinical practice and to present ways to reduce the risk of their occurrence described in the literature. Material and methods The following review of the work was based on viewable data obtained from the PubMed database and Google Scholar. The key words used in the search were: propofol, propofol infiusion syndrome, propofol bradycardia, propofol infusion pain, propofol neuroprotection, propofol hypotension. Conclusions Studies indicate a number of possible solutions to reduce the risk or intensity of individual side effects. . There are many possibilities, both pharmacological and non-pharmacological, fulfilling this task - administration of propofol simultaneously with drugs of other groups responsible for sedation, replacement of propofol with another sedation drug in selected situations, cold compresses, analgetic usage of vibrations. These methods require further research and the development of appropriate protocols for use in clinical situations.